PENGARUH KOMITMEN ORGANISASIONAL DAN KEPRIBADIAN TERHADAP KINERJA PENYIDIK RESERSE DAN KRIMINAL KEPOLISIAN RESORT KUPANG KOTA - Ridolof W. Batilmurik; Fredrik D. Belly (Pusat Riset dan Publikasi, 2021)
This research was conducted at the Kupang City Police Criminal Investigation Unit. The population in this study was 59 detective investigators in the Kupang City Police work area. The number of samples is 40 investigators. However, the return rate for the distributed questionnaires was obtained by 40 people (68%) of respondents. Meanwhile, the remaining 19 questionnaires (32%) were not returned. Data analysis technique using validity test, reliability test, normality test, multicollinearity test, autocorrelation test, heteroscedasticity test, correlation coefficient, coefficient of determination, multiple linear regression, F test and T test. The results of the analysis show that; organizational commitment indirectly has a positive and significant effect on performance; Personality directly has a positive but not significant effect on the performance of the Kupang City Police Criminal Investigator. Future research will focus on the organizational commitment of the Kupang City Police Criminal Investigator, namely; predictive, Responsibilta, Fair Transparency (Precision). In addition, it is necessary to study the work culture of the Indonesian National Police, which is very different from other organizations in Indonesia and even police organizations in other countries.